Can green technology innovation empower urban carbon mission reduction? Evidence from China - Li, Su; Cao, Xin (Frontiers in Environmental Science, 2025)
IntroductionInvestigating the relationship between green technology innovation (GTI) and urban carbon emission (CEI) is crucial for sustainable economic development and achieving the dual carbon goal.MethodsUsing panel data from 272 cities in China between 2006 and 2022, this paper empirically analyzes the impact of GTI on urban CEI by applying the fixed effects and chain mediation models. Furthermore, the chain mediating effect of environmental regulations and energy consumption structure is explored.ResultsGTI significantly reduces urban CEI, particularly in the eastern region, non-resource-based, and large-scale cities, where its carbon reduction effect is more pronounced. The mechanism analysis reveals that environmental regulations and energy consumption structure not only play an independent mediating role, but also exert a chain mediation effect.DiscussionThese findings enhance our understanding of the intrinsic mechanisms underlying green technology innovation-driven carbon emission reduction in China. Besides, they offer theoretical insights for policy formulation, demonstrating a pivotal role in environmental governance and sustainable development.